Making Shock Responsive Social Protection System in Nepalese Context - Dhakal, Thakur (Journal of Social Protection, 2020)
This paper aims to stimulate a dialogue among the policy makers on shock responsive social protection system in Nepal. In doing so, this paper highlights the improvements so as to make it responsive to shocks and disasters. A well-designed social protection as a policy, aims to protect people from vulnerability and life cycle risks as well as build resilience to shocks, which nicely complements the objectives of disaster risk management and climate change adaptation. Experiences from some countries show that a well-established, robust, and adequately funded national social protection system can quickly and efficiently respond to natural disasters and shocks. It works best in case it adopts I rights-based approach and aims for social inclusion, in addition to having political will, technical instruments and financial resources to accomplish it. This paper, specifically, reviews ongoing effort Nepal has made in making the social protection system resilient and shock responsive. It also illustrates the shortcomings and challenges and proposes some way forward.